Outcomes of Surgeries Performed in Physician Offices Compared With Ambulatory Surgery Centers and Hospital Outpatient Departments in Florida. (17th April 2017) - Ohsfeldt, Robert L; Li, Pengxiang; Schneider, John E; Stojanovic, Ivana; Scheibling, Cara M
Background: The proportion of outpatient surgeries performed in physician offices has been increasing over time, raising concern about the impact on outcomes. Objective: To use a private insurance claims database to compare 7-day and 30-day hospitalization rates following relatively complex outpatient surgical procedures across physician offices, freestanding ambulatory surgery centers (ASCs), and hospital outpatient departments (HOPDs). Methods: A multivariable logistic regression model was used to compare the risk-adjusted probability of hospitalization among patients after any of the 88 study outpatient procedures at physician offices, ASCs, and HOPDs over 2008-2012 in Florida. Results: Risk-adjusted hospitalization rates were higher following procedures performed in physician offices compared with ASCs for all procedures grouped together, for most procedures grouped by type, and for many individual procedures. Conclusions: Hospitalizations following surgery were more likely for procedures performed in physician offices compared with ASCs, which highlights the need for ongoing research on the safety and efficacy of office-based surgery.